Rising rates of wildfire building destruction in the conterminous United States - Amanda R. Carlson; Todd J. Hawbaker; Miranda H. Mockrin; Volker C. Radeloff; Lucas S. Bair; Michael D. Caggiano; James R. Meldrum; Patricia M. Alexandre; H. Anu Kramer; Paul F. Steblein (Proceedings of the National Academy of Sciences, 2025)
Many regions of the world have seen an increase in highly destructive wildfires, driven by well-documented increases in burned area and growth of housing in the wildland–urban interface (WUI), which exposes more homes to fire. However, it is unclear whether wildfires are also becoming more destructive due to changes in wildfire behavior or in the development patterns of exposed communities. Here, we assessed trends in wildfire building exposure and destruction rates in the conterminous United States from 2002 to 2022. We mapped destroyed and surviving buildings within 100 m of all wildfires that destroyed 10 or more buildings (n = 362) and assessed trends relative to major ecoregions and vegetation types. We used logistic regression to assess relationships between destruction rates and landscape factors. We found that 10% of exposed buildings were destroyed in 2002–2012, but this percentage increased to 32% in 2013–2022. This increase was largely due to greater building exposure in evergreen forests in the northwestern United States, where exposed buildings were more than 3.4 times as likely to be destroyed as those in grass and shrublands. However, annual destruction rates also significantly increased in all other vegetation types and were correlated with development type, weather, and burn severity. These results indicate that increasing wildfire destruction in the United States has resulted not only from increased exposure but from rising rates of building destruction, potentially indicating more extreme wildfire behavior. This finding underscores the need to better understand how fuel management, community planning, and hardening buildings can reduce vulnerability.